Learning Organization Practices in Empowerment District Education Office through Indicator of Change Management - Abd Rani, Nurul Sahadila; Majid, Mohamad Zuber Abd; Majid, Mohamad Zuber Abd; Hamzah, Mohd Izham Mohd (International Journal of Psychosocial Rehabilitation, 2020)
Nowadays, the effort to empower education organizations is not confined to teachers and schools, but requires the role of all parties especially District Education Office (DEO). In this regard, this study was conducted to explore the practices of learning organization in the DEO through their perspective in indicator of change management. This study was using the qualitative approach and using semi-structured interview as a data collection tool. The protocol question in this study is developing based on issue, literature review, expert opinion, and District Transformation Program 3.0 guided book. The informants were selected using purposive sampling and snowball sampling method. Analysis data in this study using thematic analysis approach with the assistance Nvivo software. The result in this study show that the themes for learning organization practices in DEO include team learning and shared vision. The successful of change in the DEO requires elements of learning organization such as team learning and shared vision. The implementation of these two dimensions in approving the learning organization will be providing positive results and added value as the process of enhancing the practices and also empowering the role of the DEO in educational organization. Thus, the finding in this study exposed that the dominant feedback from informant to empower learning organization through the team learning and shared vision to achieve a goal DEO. Further research proposals require more in-depth research on aspects related to the issues faced during the empowerment of DEO as a learning organization.